Respiratory and airway disorders in children with Down Syndrome: a review of the clinical challenges and management - Craven, V. E.; Daw, W. J.; Wan, J. W. Y.; Elphick, H. E. (Frontiers in Pediatrics, 2025)
Down Syndrome (DS), or Trisomy 21, is a common inherited chromosomal disorder, caused by an extra copy of chromosome 21, with features including intellectual disability, hearing and vision disorders, hypotonia, hypothyroidism, cardiac and gastrointestinal structural abnormalities. The characteristic features of flattened nasal bridge, mandibular and maxillary hypoplasia, relative macroglossia, and a narrow nasopharyngeal region all predispose to airway complications and structural abnormalities can extend to the lower airways and lung parenchyma. Congenital airway stenoses and malacia are present in around 1.5% children with DS and in 20% of these, there are multiple anomalies. Structural lung abnormalities include reduced alveolar numbers and altered lung architecture. The prevalence of pulmonary hypertension is a significantly increased, estimated to affect 5-10%, and increases if congenital or gastrointestinal co-morbidities are also present. The association of DS with hypotonia, increased oral secretions, gastrointestinal reflux and aspiration and obesity increase the morbidity associated with these anatomical variants contributing to poor airway clearance and increased risk of respiratory tract infections. In addition, it is been recognised that the increased risk of infections (particularly of the respiratory tract) as well as autoimmune disorders and haematological malignancies suggest a level of immunodeficiency and immune dysregulation. The anatomical features of DS predispose children to the development of sleep disordered breathing (SDB) in addition to adenotonsillar hypertrophy, the primary cause in children. Treatment options include surgery, non-invasive ventilation, and anti-inflammatory medications. Emerging techniques include drug-induced sleep endoscopy (DISE), a useful tool for assessment of the upper airway in children with OSA and to identify the additional sites of airway obstruction that may be present in DS and hypoglossal nerve stimulation for individuals resistant other treatments.